1991
DOI: 10.1177/019459989110400214
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic sinus surgery: Outcome in 155 cases

Abstract: For this retrospective study of endoscopic sinus surgery, charts of 22 patients from a medical center and 133 patients from a private practice (N = 155) were reviewed. Preoperative complaints, clinical findings, computed tomographic evidence of extent of sinus disease, surgical outcome, possible predictors of success, and complications were considered. Indications for endoscopic surgery were persistence of symptoms despite aggressive medical therapy and radiologic evidence of a significant sinus abnormality. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
44
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 5 publications
10
44
0
Order By: Relevance
“…Headache and Nasal obstruction responded the best among the symptoms. These findings are consistent with those of the other series [7][8][9][10][11][12][13][14][15][16]. 91 patients in the present study had bilateral OMU blocked, thus reemphasizing the role of OMU in the pathophysiology of CRS, as mentioned by Messerklinger [3].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Headache and Nasal obstruction responded the best among the symptoms. These findings are consistent with those of the other series [7][8][9][10][11][12][13][14][15][16]. 91 patients in the present study had bilateral OMU blocked, thus reemphasizing the role of OMU in the pathophysiology of CRS, as mentioned by Messerklinger [3].…”
Section: Discussionsupporting
confidence: 94%
“…In inexperienced hands, the major complications associated with FESS can include intracerebral haemorrhage, CSF leak, diplopia, blindness, intracranial penetration, meningitis and severe haemorrhage. Our complication rates are the same as reported by other authors [7][8][9][10][11][12][13][14][15][16]. FESS is a very effective and safe procedure when performed by surgeons experienced in the technique.…”
Section: Discussionsupporting
confidence: 87%
“…The efficacy of MMC, which remained limited in clinical studies, can be enhanced by using two doses, obviating the need for revision surgery after ESS, which was reported to vary between 7.6 and 38% [2,27] in various studies and increasing the quality of life in patients. Actually, in a clinical study carried out at a date when we obtained our initial results, it was reported that MMC administered twice, namely intraoperatively and in early post-op period, is efficacious and reliable [28].…”
Section: Discussionmentioning
confidence: 99%
“…15 In the extended study population, the number of patients who underwent revision surgery (7.4%), with an average follow-up of 1.4 years, is comparable to that seen in OR-based BSD and OR-based ESS. 8,[16][17][18] This is particularly encouraging, as most surgeons were performing their first office-based cases within this study. Revision procedures on 2 patients were performed in an office setting, suggesting that for some recalcitrant patients, repeated office-based procedures may obviate the need for an OR-based procedure.…”
Section: Discussionmentioning
confidence: 72%